Desafios da educação ambiental em uma instituição de educação profissional tecnológica - Coleto, Aline Cristina (2018)
The effects that the productive system has on the environment are increasingly important among companies, governments and educational institutions around the world. In this context, environmental education is an instrument to sensitize, raise awareness and enable change of attitudes between the academic community and employers of labor formed by the Vocational Education Training (VET). This paper aims to evaluate the challenges of environmental education in a VET institution. Its specific objectives are to demonstrate the interfaces between VET and environmental education, to identify how environmental education is present in a professional technological teaching institution in Brazil and to provide the necessary foundations for the academic community to carry out environmental education through projects, training and other instruments adapted to their reality and needs. The method of bibliographical and documentary research on the theme for elaboration of the state of the art was used. Secondary data sources, semi-structured interviews with a qualitative approach, closed questionnaries with a quantitative approach and descriptive and multivariate data analysis were used for the case study. The results show that studies on the relation between VET and sustainable development, teaching methodologies and development of skills and abilities. The interfaces between environmental education and VET consist of preparatory instrumental interface and methodological interface, and the themes also share similar limitations, identified as the necessary and constant interrelations between the worlds of theory and practice. Regarding the case study, although teachers and students understand the importance of environmental education for the training of professionals integrated to sustainable development, some of the amendments to the disciplines do not provide environmental generating themes and teachers do not have the skills to articulate environmental education in VET. Although the students understand the objectives of environmental education , they do not understand how the theme is contextualized in their technical education. In this way, the study brings unpublished contributions to the theme, analyzing the challenges of environmental education in VET, following the academic community to have to initiate and follow the implementation of environmental education in the educational routine improving its environmental, ethical and social performance.